Near-complete genome sequences of a rice necrosis mosaic virus isolate infecting rice in Argentina - Solís, V.E. (2025)
While rice necrosis mosaic virus (RNMV) has only been described in Asia, we identified this virus on a rice plant from Argentina using a viral metagenomic approach. We further confirmed this result by RT-PCR and small-RNA Illumina sequencing to obtain the near-complete genome and to confirm actual infection by RNMV.